ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN MUZAKKI PADA BAZNAS KABUPATEN SAMBAS - Ronaldi; Sumar'in; Neli (Cross-Border Journal of Business Management, 2025)
Zakat has the potential if it is, well developed, so that in the end it will be able to improve the community’s economy. Zakat is the basic principle for upholding the social structure in Islam, zakat is not charity or alms, zakat is an orderfrom Allah that must be carried out, for this reason Allah SWT esthabilises the pillars of Islam which are obligations and must be obeyed by every human being. The lack of community trust and statisfaction or muzaki is a problem for BAZNAS in Sambas regency. Most of the muzakki pay zakat directly to mustahik instead of having to pay zakat directly to BAZNAS Sambas regency, for fear that the zakat money will be misappropriated and fear that the funds will not be channeled properly.This study aims to analyze the effect of muzakki’s statisfaction and trust on the quality of BAZNAS services. This study aims to analyze the influence of satisfaction and trust of muzakki on the quality of BAZNAS services. This study is a study that uses a quantitative approach with a survey research type. The data used are primary data obtained tested with validity, reliability, classical assumption tests and then analyzed using multiple linear regression analysis techniques, T tests and F tests. The results of the study indicate that service quality does not affect the satisfaction of muzakki at BAZNAS Sambas Regency, the results of the T test, the calculated T value is 1.376 < the T table value of 1.990. Trust affects the satisfaction of muzakki at BAZNAS Sambas Regency, the results of the T test, the calculated T value is 2.730> the T table value of 1.990. Simultaneously, service quality and trust simultaneously have a positive and significant effect on the satisfaction of muzakki at BAZNAS Sambas Regency, the calculated F value is 4.767 l> from the F table of 3.11